2012
DOI: 10.1021/ef300055k
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Sugar Compounds and Uronic Acids in Enzymatic Hydrolysates of Lignocellulose Using High-Performance Anion Exchange Chromatography with Pulsed Amperometric Detection

Abstract: A method was developed for simultaneous determination of seven sugar compounds and two uronic acids by high-performance anion exchange chromatography (HPAEC) with pulsed amperometric detection (PAD) using a CarboPac PA20 column under a gradient elution (mobile phase: H 2 O/200 mM NaOH/100 mM NaAc) at 0.4 mL/min. Under these conditions, D-(−)-arabinose, D-(+)-galactose, D-(+)-glucose, D-(+)-mannose, D-(+)-xylose, D-(−)-fructose, D-(+)-cellobiose, Dgalacturonic acid, and D-glucuronic acid were all separated in 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…The results are comparable to those of other studies reported in the literature with regard to the analytical determination of carbohydrates by chromatographic methods for carbohydrates obtained from biomass samples. Compared with several current electroanalytical techniques for the assay of carbohydrates, the HPAEC‐RPAD technique bears a great advantage as a simultaneous analysis technique.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results are comparable to those of other studies reported in the literature with regard to the analytical determination of carbohydrates by chromatographic methods for carbohydrates obtained from biomass samples. Compared with several current electroanalytical techniques for the assay of carbohydrates, the HPAEC‐RPAD technique bears a great advantage as a simultaneous analysis technique.…”
Section: Resultsmentioning
confidence: 99%
“…The underlying shortcoming of these methods is that they require sample derivatization and this somewhat renders the analysis quite unwieldy . As a result, HPAEC‐High Performance Anion‐Exchange Chromatography has been more frequently employed compared to GC when it comes to carbohydrate determination in biomass.…”
Section: Introductionmentioning
confidence: 99%
“…11,12,22,23 In general, the sequence of elution of the matrix components is related to the pK a value. 11,12,22,23 In general, the sequence of elution of the matrix components is related to the pK a value.…”
Section: Optimization Of Chromatographic Parametersmentioning
confidence: 99%
“…6 Traditional methods for the detection of uronic acids are based on colorimetry using carbazole-sulfuric acid and meta-hidroxydiphenyl, 7,8 derivatizing the uronic acids to be detected. 10,11 However, this method involves a long run time, multiple dilutions of samples, and use of multiple pumps to run in gradient (consequently using large amounts of solvents for separation) and it requires the addition of a strong hydroxide post-column to minimize baseline dri. 9 Several methods have been used for the determination of sugars as well as uronic acids in lignocellulosic waste, including gas chromatography, high-performance liquid chromatography, and capillary electrophoresis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation